Proteomic Analysis of Extracellular Vesicles From Fasciola hepatica Hatching Eggs and Juveniles in Culture - Trelis, María; Sánchez-López, Christian M.; Sánchez-Palencia, Liz F.; Ramírez-Toledo, Victor; Marcilla, Antonio; Bernal, Dolores (Frontiers in Cellular and Infection Microbiology, 2022)
The identification of extracellular vesicles (EVs) in Fasciola hepatica has provided a new way to understand parasite-host communication. Most of the studies on EVs have focused on the adult stage of F. hepatica, but recently, the presence of EVs from different developmental stages has been reported. To better understand the role of EVs in the infection process and immune response modulation, the protein cargo of EVs from embryonated eggs and newly-excysted juvenile (NEJs) flukes cultured up to 28 days, has been analyzed. EVs were isolated by size exclusion chromatography and evaluated by nanoparticle tracking analysis and transmission electron microscopy. LC-MS/MS proteomic analysis of EVs revealed the presence of 23 different proteins from embryonated egg-derived EVs and 29 different proteins from NEJ-derived EVs. Most of the identified proteins had been previously described in EVs from F. hepatica adults, including cytoskeletal proteins, glycolytic enzymes, stress-related proteins and tetraspanins. Nevertheless, EVs from embryonated eggs and NEJs exhibited qualitative differences in composition, when compared to EVs form adults, including the absence of cathepsin cysteine peptidases. The differential content of the EVs released by the different developmental stages of the parasite reflect the intense activity of NEJs at this early stage, with several proteins involved in membrane traffic and cell physiology. This new set of identified proteins could help to understand key metabolic, biochemical and molecular mechanisms mediated by EVs that take place upon egg hatching and after parasite excystment.